THE STUDENTS’ PERCEPTION OF THE APPLICATIONS USED IN ONLINE LEARNING DURING COVID-19 PANDEMIC AT BORNEO TARAKAN UNIVERSITY - Haditya, Tri Muhamad Al Itiroof; Winarno, Winarno; Fitriawati, Fitriawati (Universitas Borneo Tarakan, 2023)
This research aimed to describe students’ perception of efficient applications used in online learning at the English Education Department of Borneo Tarakan University. This research was quantitative research with 32 English Education respondents in the Borneo Tarakan University. The sampling method used was total sampling. The instrument used was a questionnaire. The results of the research indicated that the applications used in online learning amid the COVID-19 pandemic were very efficient because these applications provided a good way or alternative for supporting the learning activities from home. Students used various online learning applications. The applications used are considered efficient enough to help the learning process and can improve English skills, especially students’ speaking skills. Applications used during online learning also facilitate learning because of easy access in the low network coverage setting, not using too much internet bundlest, and economical and suitable enough features to support the learning process. Even though it supports the learning process, some students still find some difficulties with the applications used in online learning.